The interpellation of inclusion policies to school grammar of the Argentinian high school - Melendez, Cecilia Evangelina; Yuni, José Alberto (Education Policy Analysis Archives, 2019)
In this article it is proposed a theoretical- analytical reading about the manner in which inclusion policies in Argentinian high school interpellate school grammar during the last decade. In theory it is discussed the extent of the idea of interpellation; this permits the study of education policies and their effects in terms of performative manner and affectation to school logic, its production rules and functioning. School grammar it is conceptualized as a main source that generates and structures practices, identities and school discourses through which senses about schooling are built. According to this work's theoretical hypothesis, inclusion policies were directed to destabilize the components of that main generative source. In order to achieve this objective, the principal norms and actions of education policies trying to institutionalize new senses to this level are exposed. Such policies produced an interpellation to school ideology of school grammar that normalizes and classifies the subjects. The normative political changes having tendency to inclusion (in social, pedagogic and cultural dimensions) introduced a tertiary form that interpellates the main source of school grammar, which is organized in binary pairs of hegemonic opposed subordinates. That interpellation enables the arising of new cultural ideals and subjective and other institutional identifications.